THE SIGNIFICANCE OF THE SWISS CARBON TAX ON ECONOMIC GROWTH: A GREEN ECONOMY PERSPECTIVE - Faisal Nurdin Idris; Khairunnisa T. Syakura; Dewi S. Syifaunnajah; Shalwa D. Gemilang (Journal of Social Political Sciences, 2025)
This study analyzes the significance of a carbon tax for economic growth in Switzerland from a green economy perspective. Through environmental fiscal policy, Switzerland seeks to encourage business routine (business as usual) into a transition towards a low-carbon economy. This study uses a descriptive qualitative method to analyze data from available scientific publications on carbon taxes in Switzerland. Drawing on a green economic perspective, including the Pigouvian tax concept, the marginal social cost of carbon, and the double dividend, this study found that the Swiss carbon tax has double positive benefits. The Swiss model of a carbon tax facilitates efforts to reduce carbon dioxide emissions while simultaneously maintaining economic growth. This condition is achieved through a plan that is designed adaptively and transparently, incorporating a revenue recycling mechanism. The implementation of the carbon tax balances economic growth with environmental sustainability and social justice to ensure a just and sustainable green transition